2x(x-1)+9(x-1)=0

Simple and best practice solution for 2x(x-1)+9(x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x-1)+9(x-1)=0 equation:



2x(x-1)+9(x-1)=0
We multiply parentheses
2x^2-2x+9x-9=0
We add all the numbers together, and all the variables
2x^2+7x-9=0
a = 2; b = 7; c = -9;
Δ = b2-4ac
Δ = 72-4·2·(-9)
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{121}=11$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-11}{2*2}=\frac{-18}{4} =-4+1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+11}{2*2}=\frac{4}{4} =1 $

See similar equations:

| 5/x+1-3/×-1=7/×(×)-1 | | X²+y²=185 | | 5x(3x+8)-6(3x+8)=0 | | 1/6y+3=5 | | (2.1/3.5)=(x/60) | | 1/3x-25=-22 | | 5=10(x-3) | | 12+–2m+5=–1= | | 31617=x+0.2x | | 3465=35(p+20) | | x*(8-x)=-115 | | 3465=35(p+20 | | 7/5y+28=56 | | 1/x=5/2x+4 | | 7|5y+28=56 | | x/x+3=6+10 | | x^2-8x-115=0 | | 3(x+2)–4=11 | | x²-8x-115=0 | | n/12=2 | | 0.003(9-k)+0.05(k-6)=1 | | -2(x+5)+6x=3(x+1)+x+7 | | 15-8a=8a | | 2w+24=54 | | Y=x+0.2x | | 6y-39=-9 | | 6=7-m+7m-9 | | 5x-3-4x+2=9x+3 | | 0.003(3-k)+0.04(k-4)=1 | | 12x^2+3x-15=0 | | W-(3x-4)=2x-9 | | 2x+7=1x+8 |

Equations solver categories